If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -45 = 9 Reorder the terms: -45 + 3x = 9 Solving -45 + 3x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + 3x = 9 + 45 Combine like terms: -45 + 45 = 0 0 + 3x = 9 + 45 3x = 9 + 45 Combine like terms: 9 + 45 = 54 3x = 54 Divide each side by '3'. x = 18 Simplifying x = 18
| 39=54-5r | | 60=7x+4 | | 6n+4=-20 | | 47=5x-3 | | 25*5=125 | | 73-18= | | 12x-100=5x-9 | | 110=10(2x+9) | | m^2+m=100 | | 1/2x-7/6=53/6-1/3x | | 0.9x-1.1=0.3+0.2x | | 2/3x=1/6x+2 | | 5t^2=5 | | 2/3(x+3)=5/4x+17/12 | | 12(7+5y/2)^2-5y=72 | | 1/2(x-2)=2/3x-6 | | 2x^2+7=20.52 | | 40-4x=50+23 | | 5x-6=(2x-3) | | 9(x-2)=-6(4-x)+8 | | -2.9x=31.2 | | 4+(x-3)=5-7 | | 1=10+3x | | 8(3x-5)-4(2x+3)=12 | | 25=4x-3 | | X+x/4=15 | | 5=15+2x | | 8=4x-2 | | 6xy-9yx+4xy= | | 5x*5y=32 | | a+5+2a-2= | | 5p-8=3(4-p) |